Development of a time-resolved fluoroimmunoassay of CFP-10 for rapid diagnosis of tuberculous pleural effusion. Issue 4 (July 2015) - Lu, Jianyi; Zou, Lilin; Liu, Bin; Li, Xiaoqing; Tan, Jinrong; Zhao, Ai; Xiong, Chunhui; Li, Xiang; Lu, Jianxin; Gao, Jimin
Summary Tuberculous pleural effusion is the second most common form of extrapulmonary tuberculosis, which is very difficult to rapidly distinguish from malignant pleural effusion in the clinical setting. A time-resolved fluoroimmunoassay (TRF) of CFP-10, a low molecular weight protein secreted by pathogenic Mycobacterium tuberculosis, was developed to differentiate tuberculous pleural effusion from malignant one. The measuring range was 0.3–187.5 ng/ml with the dose–response coefficient of 0.9998 and detection limit of 0.036 ng/ml. The intra-assay and inter-assay coefficients of variation were 3.6–9.2% and 10.0–12.4%, respectively. The concentration of CFP-10 in malignant pleural effusion was less than 0.8 ng/ml. The negative predictive value was 93.1% in malignant pleural effusion (n = 247) while the positive predictive value was 83.0% in tuberculous pleural effusion (n = 235). Moreover, there was a statistically significant difference in the CFP-10 concentration of pleural effusion between the groups before and after clinical therapy of tuberculosis (P < 0.001, n = 81). In addition, the stability of the diagnostic reagents lasted at least 1 year at 4 °C. Therefore, the TRF of CFP-10 may be used for the rapid diagnosis of tuberculous pleural effusion and further monitoring the clinical therapeutic efficacy of tuberculosis.